Validation of Three Different Sterilization Methods of Tilapia Skin Dressing: Impact on Microbiological Enumeration and Collagen Content - Ibrahim, Ahmed; Hassan, Dalia; Kelany, Noura; Kotb, Saber; Soliman, Mahmoud (Frontiers in Veterinary Science, 2020)
Tilapia fish skin has demonstrated promise as a stable and practical biological dressing to be used in wound and burn management. However, the appropriate sterilization technique of the Tilapia fish skin is crucial before its clinical application. The standard sterilization technique must eliminate harmful pathogens but maintain the structural and biochemical properties that could compromise the dressing function. This study investigated and compared the efficiency of three sterilizing agents; chlorhexidine gluconate 4% (CHG), povidone iodine 10% (PVP-I), and silver nanoparticles (25µg/mL) (AgNPs), at three different times (5, 10, and 15 min) on Tilapia fish skin based on the microbial count, histological and collagen properties. Among the sterilization procedures, AgNPs showed rapid and complete antimicrobial activity, with a 100% reduction in microbial growth of the fish skin throughout the treated times. Furthermore, AgNPs did not impair the cellular structure or collagen fibers content of the fish skin. However, CHG and PVP-I caused alterations in the collagen content. This study demonstrated that the AgNPs treatment of Tilapia fish skin provided sterile skin while preserving the histological properties and structural integrity. These findings provide an efficient and quick sterilization method suitable for Tilapia fish skin that could be adopted as a biological dressing.